Pregnancy Tradition Ceremony in Javanese Society - Zulkifli Zulkifli; Yenni; Dila Yulinda Sari; Angeline Rachel; Elland Sasihade (Indonesian Journal of Medical Anthropology, 2023)
Javanese is one of Indonesia's main ethnic groupings. In daily life, Javanese culture influences people's conduct, particularly the custom of maternal care. During pregnancy care, the Javanese adhere to their predecessors' traditions, which have become generations-old customs. This article employs a literature review approach to describe the behavior of Javanese people in carrying out pregnancy care according to Javanese culture. Many Javanese continue to believe in and adhere to maternity care traditions because they feel these cultural customs and practices benefit pregnant women. Not only are pregnant women educated about pregnancy care, but so may their husbands.